Creating a Self-Service Food Ordering Application for a Fried Chicken Restaurant Based on a Website Using Golang, React APP, and MySQL - Alfian Subaru Putra; Farid Thalib (Magister Administrasi Bisnis ULM, 2026)
Abstract: A website-based food ordering application has been developed using the Vite Js framework from React Js for the frontend and Golang for the backend, which is integrated with a MySQL database. The purpose of this research is to create an efficient and responsive application with key features such as viewing menus, adding items to the cart, checking out, paying with MidTrans, and viewing payment details. This application can only be used for online ordering and takeaway food pickup. The System Development Life Cycle (SDLC) method was used to accelerate the development process with a focus on user needs. The results of the study show that the application not only meets the basic needs of food ordering but also provides a role-based system to limit frontend and backend integration without constraints. This application has been tested using the Black Box method, Browser Testing on three devices with different screen sizes and no component stacking. As well as User Acceptance Test (UAT) with an average result of 84.82%, so it can be said that this application can run well to facilitate restaurant menu ordering